Arguments mobilisés par des étudiants universitaires lors de la discussion d'une controverse entourant la vaccination contre le papillomavirus - Abdelkrim Hasni; Nancy Dumais (Université de Provence, 2022)
We conducted a study to introduce university students to understanding socioscientific controversies by considering the case of human papillomavirus (HPV) vaccination. To describe this understanding, we used a conceptual framework based on the didactic of Questions scientifiques socialement vives and the current works of socioscientific issues and controversial issues as well as on the concept of socioscientific controversies inspired by the sociology of science. Methodologically, a questionnaire was filled out by each student, and then all students were engaged in teams in a debate initiated by analyzing two short articles defending different positions on vaccination. The results show the role of the debate in the emergence of a diversity of categories of arguments that highlight the controversy's leading scientific and social issues. These results also highlight the need for explicit teaching of these issues to enable students to develop a multidimensional and informed understanding of the controversy.